Answer:
3.- The same
Step-by-step explanation:
1.- In the reactants you need to calculate the charges that you have:
2 Al(s) = zero, because the aluminum is in it based formed (that mean without charge).
3 Cu2+ = 3 x 2+ = 6+ That is the total positive charges that copper collaborate in this reaction.
2.- Then calculate the charges on the products:
2 Al3+ = 2 x 3+ = 6+ charges from the aluminum.
3 Cu(s) = zero, because the copper in this case is in the base form
3.- In this way, the charges at the begging (6+) and at the end (6+) are the same.